(untitled) (Journal of Human Sciences, 2021)
Poetry does not present an absolute, clear truth. It presents a probabilistic, confused meaning, as the poet does not use the language in its normal lexical meaning, rather s/he uses poetry figuratively, removing the word from its conventional lexical meaning, to give it a new meaning, which it gains from the context of the speech. The context determines the word’s meaning, not the lexicon or the habit. Hence, the word changes its ordinary meaning and gains a new meaning in poetry, which the reader may not be entrusted with, and the language itself helps in this matter because it accepts the figurative meaning. The meaning, in this case, is neither definitive nor final, but rather probabilistic, because the language used in the production of the text does not present the meaning as a lexical semantic presentation of the word, but rather suggests. Therefore the text is open to several possibilities and interpretations of the meaning. That is, the meaning is not predetermined. The text accepts this meaning or that meaning by the nature of its probabilistic language. This means that the reader has the opportunity to reproduce the meaning and the text. The reader gives meaning to the existence of the text. The meaning that the poet produced the text to express with its something or an event or a situation. The reader can reproduce the text and load it with the semantic meaning that s/he wants to express by the language. This process would not exclude the potential meanings of the text. The metaphor used in the production of the text is open to several readings and interpretations. By this process, the lexical meanings of the words are circumvented, just as the meanings acquired by the words through their uses in the texts achieved by previous historical stages circumvented.